Exploring theoretical mechanisms and perspectives - Perrewe, Pamela L.; Ganster, Daniel C. (JAI, 2001)
The series Occupational Stress and Well-Being spans a number of traditional disciplines which include psychology, medicine, sociology, anthropology, management and business. It represents a serious attempt to bring these disciplines together to advance the field and study of occupational stress. This volume focuses on promoting theory and research perspectives on significant topics in occupational stress and well-being.
Keywords: Job stress.; Job stress -- Treatment.; Stress (Psychology); Business & Economics -- General.; Science -- History.; Occupational & industrial psychology.; elektronické knihy; electronic books